2020
DOI: 10.18267/j.pep.744
|View full text |Cite
|
Sign up to set email alerts
|

Commuting Time and Life Satisfaction of High School Students in the Czech Republic, Italy and Slovenia

Abstract: This study is a contribution to research into the relationship between commuting and life satisfaction. Our focus is on high school students. The research is based on a questionnaire survey among students in three countries: the Czech Republic, Italy and Slovenia. The analysis is conducted using six OLS regression models: three countries and both boys and girls in each country. The results show significant variance between the countries as far as the relation between commuting time and life satisfaction is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…More concretely, life satisfaction previously has been associated with school-level factors, such as type of school, school size, teacher qualification [ 66 ], school stress [ 67 ], school engagement [ 6 ], school performance [ 68 ], class climate [ 69 ], and others. Our results on school commuting did not support previous studies of adults [ 47 , 48 ] or adolescents [ 15 ]. However, children who are accompanied to a school rated their journeys as happier compared to their unaccompanied counterparts [ 70 ], suggesting that more research is needed on independent mobility from the adolescents’ perspective.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…More concretely, life satisfaction previously has been associated with school-level factors, such as type of school, school size, teacher qualification [ 66 ], school stress [ 67 ], school engagement [ 6 ], school performance [ 68 ], class climate [ 69 ], and others. Our results on school commuting did not support previous studies of adults [ 47 , 48 ] or adolescents [ 15 ]. However, children who are accompanied to a school rated their journeys as happier compared to their unaccompanied counterparts [ 70 ], suggesting that more research is needed on independent mobility from the adolescents’ perspective.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research has shown that time spent on daily activities plays an important role in adolescents’ life satisfaction [ 14 , 15 , 16 , 17 ]. Moreover, recent studies have suggested that the amount of time adolescents spend on daily activities has changed in the last decades [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is still unclear whether the coming of the pandemic has affected the importance of concrete factors of life satisfaction. Janáček and Rybáček (2020) have shown that factors of life satisfaction differ significantly across countries. Thus, it is possible that they also differ when we take into account one country across different time periods.…”
Section: Literature Reviewmentioning
confidence: 99%